Effect of TMCP on Microstructure and Mechanical Properties of 304 Stainless Steel. Issue 8 (13th May 2018) - Mallick, Pratik; Tewary, Nisith Kumar; Ghosh, Swarup Kumar; Chattopadhyay, Partha Protim
Abstract : The present study investigates the evolution of microstructure and mechanical properties of 304 stainless steel after thermo‐mechanical controlled processing (TMCP). Three different FRTs (finish rolling temperatures) have been adopted and the micro‐constituents are identified as austenite grains, stacking faults, annealing, and deformation twins. Fine austenite grains in the range of 1–30 μm are obtained at lower FRT (700 °C) whereas at higher FRT, coarse grains are formed. TEM and X‐ray analyses indicate the formation of M23 C6 ((Cr, Fe)23 C6 ) precipitates for higher FRT (900 °C). Specimen processed with 700 °C FRT results into 37% enhancement in UTS compared to the base metal which is attributed to fine partially recrystallized grain, extensive deformation twinning and high dislocation density. Maximum elongation (68%) is obtained due to the formation of strain‐free equiaxed grains (≈40 μm) at 900 °C FRT. Abstract : The present study deals with the microstructure and mechanical properties of TMCP processed 304 stainless steel. Fine austenite grains are obtained at lower FRT (700 °C) and M23 C6 ((Cr, Fe)23 C6 ) precipitates have been observed in higher FRT (900 °C). 700 °C FRT results in 37% enhancement in UTS compared to the base metal, whereas maximum elongation (68%) is obtained at 900 °C FRT.